Rumination and self-control interact to predict bulimic symptomatology in college students. (August 2016) - Breithaupt, Lauren; Rallis, Bethany; Mehlenbeck, Robyn; Kleiman, Evan
Abstract: Recent studies suggest that a ruminative response style may contribute to the development and maintenance of Bulimia nervosa. However it is not clear what factors may contribute to the relationship between rumination and BN. One factor may be self-control, as studies suggest that BN symptomatology relates to deficits in self-control. In the present study, we hypothesized that the association between rumination and BN symptomatology would be the strongest among individuals with lower self-control relative to those with higher self-control. Participants were 353 students at a large university. Participants completed measures of self-control, rumination, and eating disorder symptomology as part of an online study. A hierarchical regression supported an interaction between rumination and self-control predicting bulimic symptomatology, controlling for BMI. Individuals with higher levels of rumination presented more bulimic symptoms if they also had lower levels of self-control, supporting our hypothesis. Based on these findings, assessing rumination in conjunction with self-control among individuals who present with eating concerns may help to direct treatment. Additionally, clinical interventions increasing self-control may also alleviate some BN symptoms in ruminators. Highlights: Self-control moderates the relationship between rumination and bulimic symptomatology. The association between rumination and bulimic symptoms was strongest among subjects with lower self-control. Analyses indicate that the bulimic symptoms had a specific relationship to rumination and self control.